Developing PBL-based worksheet to foster self-confidence and problem-solving skills in learning transformation geometry - Santi Nurhidayanti; Burhanudin Arif Nurnugroho (International Journal on Education Insight, 2026)
This research aims to develop a valid and practical Problem-Based Learning (PBL) student worksheet to facilitate them fostering their self-confidence and problem-solving skills in learning transformationa geometry. Using the ADDIE model, this research involved 20 ninth-grade students of a private junior high school in Yogyakarta to learn the concepts of reflection and rotation using the worksheet. The worksheet integrates PBL syntax, self-confidence descriptors, and Polya's problem-solving indicators. The validation by experts and teachers yielded an average score of 90.36% (very high), while the students’ response on the worksheet practicality yielded an averagfe scores of 90% (small group) and 88.75% (large group). The scores mark a very practical indicator of the worksheet. The existence this worksheet enriches the best practices of the efforts to foster self-confidence and problem-solving skills among students.